Pemantauan Kondisi Ikan Karang Menggunakan Metode Reef Check Di Perairan Selat Sempu Malang Selatan - Luthfi, Oktiyas Muzaky; Alifia, Riza; Putri, Sherla Rizqia; Dasi, Firmina Bethrix; Putra, Bramastrha Artha; Permana, Davitra Eka; Pebrizayanti, Elda; Fikri, Muhammad Zuhal; Saputro, Johan; Setiawan, Christopher Ari; Sibuea, Krista; Razak, Abdul (Journal of Marine and Aquatic Sciences; Vol 3 No 2 (2017), 2017)
Reef Check is an activity to find out the condition of coral reefs and its surrounding ecosystems be then described and categorized its healthiness. The island of Java is one of the Islands in Indonesia that has lots of beaches, especially for East Java, here they have several areas that has become our research site in Sempu Strait, Sendang Biru, South Malang they are called Teluk Semut, Watu Meja, and Waru-waru. Underwater Visual Census (UVC) was used as a method for this research to identify reef fish in a transect of 100 x 5 x 5m scale in (Length, Width, and Height). Results shows several fishes was used to identify yet the family of  Chaetodontidae with mean abundance 8 in Teluk Semut 1 station, 2.25 in Teluk Semut 2 station, 12.5 in Rumah Ikan station, & 13.5 in Watu Meja station. Watu Meja and Fish Apartment station shows higher mean abundance than other station, this indicates coral reefs ecosystem in this station have a better health & condition compare to the other stations. Results for family family Haemulidae , Snapper and Grouper shows low mean abundance, that indicates overfishing on Sempu Strait, South Malang. In other cases, the purposes of Reef Check is to determine the extents of human activities and its impact against the distribution and the healthiness of coral reefs in the area. For further extent, there has been still indications toward its management system yet fisheries potential in certain areas for this research.